An overview of the methodological aspects and policy implications of willingness-to-pay studies in oral health: a scoping review of existing literature - Navid Saadatfar; Mohammad Pooyan Jadidfard (BMC, 2020)
Abstract Background Demands for dental services seem to be beyond the capacities of most healthcare systems these days. Patient preferences have been increasingly emphasized to be considered in the joint decision-making process. Willingness-to-pay (WTP) is a recommended method for measuring the utility of health services; increasingly being used in recent decades. Taking these points into consideration, this article aims to provide an overview of the methodological aspects and policy implications of WTP studies in the field of oral health. Methods The research was conducted in ISPOR, PubMed and Google Scholar databases. In addition, reference lists of included articles were checked to identify the relevant studies. All studies published were included that were in the English language and reported using WTP for oral health-related goods and services. A data-charting form was developed by a focus group discussion panel of seven experts to derive the main methodological aspects of WTP. Also, Core policy suggestions were categorized through thematic content analysis of the included papers. Results The search strategy yielded 389 studies of which 52 were included. WTP studies in oral health show an increasing trend in global publications. The UK and Canada have a greater share in published material than in any other country. The dominant field of these researches is in restorative and prosthetic dentistry, and a wide range of different methodological aspects was documented. Policy suggestions were categorized in three main themes: (A) setting new tariffs or subsidizing the item, (B) provision of the item due to population preferences, and (C) improving literacy regarding the item. Conclusions An urgent need for a common framework regarding the design of WTP studies in dentistry seems paramount. Some policy suggestions seem not to be applicable, perhaps due to insufficient familiarity of the researchers with the complexities of the public policymaking process.